Способ получения 2,6-диацетил-1,5-ди(R)-2,4,6,8-тетраазабицикло[3,3,0]октан-3,7-дионов - Яговкин А. Ю. Александр Юрьевич; Бакибаев А. А. Абдигали Абдиманапович; Филимонов В. Д. Виктор Дмитриевич
опубл. 15.10.94, Бюл. № 19